Hybrids versus parental species: insights from wing phenotype similarities and differences in triatomine insects - Lara, Álvaro; Hernández, María Laura; Yumiseva, César A.; Grijalva, Mario J.; Villacís, Anita G. (Frontiers in Insect Science, 2025)
IntroductionThe genus Panstrongylus is one of the most important within the subfamily Triatominae, which includes vectors of Trypanosoma cruzi, the etiological agent of Chagas disease (CD). In particular, Panstrongylus chinai and P. howardi have drawn attention for their role in disease transmission. These species exhibit notable ecological and morphological differences. Previous studies have investigated aspects such as morphometry, cytogenetics, and ecological niches, including experimental crosses between these species that resulted in viable F1 hybrids. However, no F2 generation was produced, as the eggs laid were empty and failed to hatch, limiting the study to F1 hybrids.MethodsWe analyzed wing morphometric traits (size and shape) from 262 individuals, including P. chinai, P. howardi, and their hybrids, using geometric morphometry techniques. This study aimed to build upon previous findings by analyzing the wing morphometric and environmental adaptations of P. chinai, P. howardi, and their hybrids (♀P. howardi × ♂P. chinai) to determine whether the hybrids exhibited similarities in wing size and shape, regardless of maternal or paternal phenotype.ResultsDifferences in centroid size were observed between the parental species, with P. howardi having a larger size, but no significant differences were found among the hybrids. Females showed greater shape similarity between P. howardi and the ♀P. chinai × ♂P. howardi hybrids, while males showed similarity among hybrids. Discriminant analysis was more effective for distinguishing parental groups than with hybrids. The K-means algorithm successfully classified the parental species and hybrid groups, although with low assignment percentages and a different number of groups than expected.DiscussionThe smaller wing size in hybrid offspring may indicate lower fitness, potentially due to genetic effects or reduced viability. Geometric morphometry effectively distinguishes parental species from hybrids, supporting previous research in Triatominae. The study suggests that environmental and reproductive pressures may influence these species and explores the dispersive capabilities of triatomines, contributing to the understanding of hybridization processes.